CAN A TRANSLATION EVER BE TRULY NEUTRAL, OR IS EVERY TRANSLATION AN ACT OF INTERPRETATION? - Ugiloy Karimova (Bright Mind Publishing, 2025)
The inquiry into whether translation can achieve complete neutrality or if it is intrinsically an interpretative act has engaged scholars, practitioners, and theorists for centuries. Translation transcends a mere word-for-word conversion; it constitutes a multifaceted negotiation of meaning across various cultural, historical, and ideological frameworks. This article examines the degree to which theoretical neutrality in translation is feasible and practically achievable. Utilizing a mixed-methods approach, it juxtaposes case studies drawn from legal, political, literary, religious, and machine-assisted translation domains. The results indicate that, although efforts toward neutrality are particularly evident in legal and technical fields, true neutrality remains unattainable. Translators unavoidably influence meaning through their choices of vocabulary, syntactic constructions, cultural contexts, and even through omissions. Furthermore, machine translation, frequently regarded as impartial, perpetuates human biases that are present in the training data. The discourse posits that translation ought not to be assessed based on the fallacy of neutrality but rather on criteria such as transparency, accountability, and an acknowledgment of its inherently interpretative character. This research advances discussions within translation studies, applied linguistics, and digital humanities by redefining neutrality as a myth and positioning interpretation as the fundamental action of translation.
Keywords: Translation studies, neutrality, interpretation, legal translation, political discourse, literary translation, sacred texts, machine translation, translator visibility, cultural mediation, ideology in translation, AI bias.